ANALYSIS OF WORK POSTURE AMONG OPERATORS AT CV. ADILA JAYA USING THE RULA AND REBA METHODS - Muhammad Roby Iskandar; Siti Fatimah Azzahro; Dwi Kania Oktaviani; Budiharjo (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2025)
Workplace ergonomic risks significantly impact operator health and productivity, especially in small-scale manufacturing like CV Adila Jaya’s hotel sandal production. This study aims to analyze operator working postures using Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA) methods. A descriptive quantitative design was employed with purposive sampling of operators active in five production stages: measuring and molding, cutting, printing, assembling, and packing. Data were collected through direct observation, photographic documentation, and the Nordic Body Map (NBM) questionnaire to assess musculoskeletal complaints. Postural risks were quantified using RULA and REBA worksheets. Results indicated very high to high ergonomic risk levels particularly in measurement, molding, cutting, and packing stages. Musculoskeletal complaints mainly involved the neck, shoulders, back, and upper limbs. The study concludes that ergonomic interventions are urgently needed to improve working postures and reduce musculoskeletal disorders. Continuous ergonomic assessment and workstation redesign should be implemented to enhance operator comfort, reduce injury risk, and improve productivity in small-scale industries.